Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/bib/bbt086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of software packages for detecting differential expression in RNA-seq studies

Abstract: RNA-sequencing (RNA-seq) has rapidly become a popular tool to characterize transcriptomes. A fundamental research problem in many RNA-seq studies is the identification of reliable molecular markers that show differential expression between distinct sample groups. Together with the growing popularity of RNA-seq, a number of data analysis methods and pipelines have already been developed for this task. Currently, however, there is no clear consensus about the best practices yet, which makes the choice of an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
350
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(384 citation statements)
references
References 28 publications
(55 reference statements)
14
350
0
11
Order By: Relevance
“…Using linear models for microarray analysis (LIMMA), we looked at differentially expressed genes between the CD49f Hi and CD49f Lo populations (36). A total of 1,501 genes were differentially expressed between the CD49f Hi and CD49f Lo populations, with 527 genes up-regulated in the Hi population and 923 genes up-regulated in the Lo population.…”
Section: Benign and Cancer Gene Expression Profiles From The Same Epimentioning
confidence: 99%
“…Using linear models for microarray analysis (LIMMA), we looked at differentially expressed genes between the CD49f Hi and CD49f Lo populations (36). A total of 1,501 genes were differentially expressed between the CD49f Hi and CD49f Lo populations, with 527 genes up-regulated in the Hi population and 923 genes up-regulated in the Lo population.…”
Section: Benign and Cancer Gene Expression Profiles From The Same Epimentioning
confidence: 99%
“…The results presented here are based on synthetic datasets to allow controlled experiments and exploration of a widerange of parameters, with no emphasis on a particular application. Note that these comparisons are not meant to serve as a benchmark (more sophisticated comparisons and benchmarks can be found in other studies [6,11,16,[18][19][20][21]28]) but instead to motivate the need for and the specific design decisions in EDDA. In the following section, we discuss the validity of the modeling assumptions and parameter ranges that we investigated and used to guide the design of EDDA.…”
Section: Resultsmentioning
confidence: 99%
“…The digital nature of associated data has allowed for several model-based approaches including the use of exact tests (for example, Fisher's Exact Test [11]), Poisson [17], and Negative-Binomial [6,12] models as well as Bayesian [15] and Non-parametric [16] methods. Recent comparative evaluations of DATs in a few different application settings (for example, for RNA-Seq [6,16,[18][19][20][21] and Metagenomics [11]) have further suggested that there is notable variability in their performance, though a consensus on the right DATs to be used remains elusive. In addition, it is not clear, which (if any) of the DATs are broadly applicable across experimental settings despite the generality of the statistical models employed.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, no differences have been found in the final results between various methods (Seyednasrollah et al 2015).…”
Section: Normalizationmentioning
confidence: 96%